2011
DOI: 10.1097/mej.0b013e32834490dc
|View full text |Cite
|
Sign up to set email alerts
|

Parental presence during invasive procedures in a Spanish pediatric emergency department

Abstract: Most of the parents wish to stay beside their children during IPs. In our PED, parents were present for more than 95% of IPs. The more invasive the procedure is, the more anxious parents feel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“… 13 According to Gamell et al, most of the parents wish to stay beside their children during invasive procedures. 14 Furthermore, they also reported that 51.6% of the respondents in their study believed that parents should decide on their own whether their presence was desirable. These findings from different studies obviously demonstrate that parents should be included in all steps of a child's treatment process.…”
Section: Discussionmentioning
confidence: 85%
“… 13 According to Gamell et al, most of the parents wish to stay beside their children during invasive procedures. 14 Furthermore, they also reported that 51.6% of the respondents in their study believed that parents should decide on their own whether their presence was desirable. These findings from different studies obviously demonstrate that parents should be included in all steps of a child's treatment process.…”
Section: Discussionmentioning
confidence: 85%
“…Also, only 51.6% of parents believed that they should have the choice to be present. 20 This discrepancy in responses, particularly between the desire to stay and to have the choice to be present, may be attributable to many factors, including differences in culture, facility resources and institutional guidelines, but warrants further investigation into reasons behind each desire and how those desires might be reconciled.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, family members are supportive of FPDR in adult and pediatric patients (11,16,20,48,(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66). Even families who would not want to be present often believe they should at least be given the option (20,54,61).…”
Section: Family Membersmentioning
confidence: 99%
“…In the pediatric setting, physicians were generally more supportive of FPDR and invasive procedures (37)(38)(39)(40)(41)(42)(43)(44). FPDR has been a well-established practice in Canada and the United States in the pediatric realm and, thus, most studies in which physicians were opposed to family presence were conducted outside of North America (45)(46)(47)(48)(49)(50). Almost all studies investigating nursing attitudes toward FPDR in pediatrics were supportive of the practice, especially in the intensive care unit (38,39,42,43,51,52).…”
mentioning
confidence: 99%